Artificial-intelligence robot umpires in sailing race - Wu, Chien-Hung (Frontiers in Psychology, 2022)
Today, many maritime nations have been promoting boat sports proactively, including sailing races. As sailing races are large-scale regattas that require massive workforces to monitor the game fairly; however, with limited match budgets and labors, Internet of Things (IoT) technology supports to monitor games has become a trend. This article proposes a robot umpire system in sailing race based on Artificial Intelligence (AI) techniques, using drones and AIoT technology to monitor sailing matches. When a large number of sailboats are in a match, and each sails along different routes, drones can monitor the entire game simultaneously. The features of this proposed approach are: 1. The system recognizes images by Faster R-CNN, judging whether a sailboat uses a motor to accelerate; 2. The system detects conditions by edge computing; when cheating behaviors happen, it can notify the event holder immediately; 3. Advanced drone route plans can avoid collision incidents; 4. Improve the system recognition by federated learning. This study has implemented an experiment with real drones and installed IoT equipment on the drones for taking videos and recognizing. The experimental result has shown that the proposed approach is feasible and benefits the match’s fairness. Additionally, umpires can review the violation details from the videos taken by the drones, supporting evidence for judging.